ANALISIS PRAGMATIK TERHADAP BENTUK EKSPRESI PENERIMAAN DALAM DIALOG ANTARSANTRI DI PESANTREN - Mukhamad Miftakhudin Wildani; Farida Yufarlina Rosita; Berlian Pancarrani (Cahaya Ilmu Bangsa Institute, 2025)
This study analyzes the forms of expressions of acceptance in dialogues between students in Islamic boarding schools from a pragmatic perspective. This study aims to identify various expressions of acceptance used by students in daily interactions and to understand how the social and cultural context of Islamic boarding schools influences the use of these expressions. Using a qualitative approach, data were collected through observation and recording of conversations that occurred in the Islamic boarding school environment. The results of the study indicate that expressions of acceptance can be manifested through various forms, including direct speech such as